United States : 2016 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2016)
This 2016 Article IV Consultation highlights that the United States is now in its seventh consecutive year of expansion. The unemployment rate has fallen to 4.9 percent, and household net worth is close to precrisis peaks. Nonetheless, the economy has gone through a temporary growth dip in the last two quarters. Lower oil prices led to a further contraction in energy sector investment, and a strong dollar and weak global demand have weighed on net exports. With activity indicators for the second quarter of 2016 rebounding, the economy is expected to grow at 2.2 percent and 2.5 percent in 2016 and 2017, which is above potential.